A new president in the White House: implications for Canadian agricultural trade. (4th February 2021) - Grant, Jason H.; Boys, Kathryn A.; Xie, Chaoping
Abstract: Canadian agricultural trade has experienced several volatile periods over the past 15 years. The Great Recession (2007–2009), the 2015–2016 global trade slowdown, unilateral policy actions by the United States against key trade allies and the multilateral system more generally, and the impacts of the Covid‐19 pandemic are among the most significant events during this period. Given the close integration of Canadian and US agricultural markets, the recent US election is likely to again impact the relative competitiveness of Canadian agricultural exports. While many observers suggest President‐elect Joe Biden will return to normal times regarding multilateral cooperation with key allies and international institutions such as the World Trade Organization, the new administration is likely to face headwinds given the significant fraying of ties with key trading partners and allies due to disruptive actions taken by his predecessor. This article provides an overview of potential implications of a Biden administration for Canada's agricultural trade. We start by reviewing recent trade shock events affecting Canada's agricultural trade with a particular focus on trade actions taken by the United States. Relevant components of the President‐elect Biden's platform, considerations affecting the implementation of this platform, and the implications of this for Canadian agricultural trade are considered. Abstrait: Le commerce agricole canadien a connu plusieurs périodes de volatilité au cours des 15 dernières années. La Grande Récession (2007‐2009), le ralentissement du commerce mondial en 2015–2016, les mesures politiques unilatérales des États‐Unis contre les principaux alliés commerciaux et le système multilatéral en général, et les impacts de la pandémie de Covid‐19 sont parmi les événements les plus importants durant cette période. Compte tenu de l'intégration étroite des marchés agricoles canadien et américain, les récentes élections américaines auront vraisemblablement à nouveau une incidence sur la compétitivité relative des exportations agricoles canadiennes. Alors que de nombreux observateurs suggèrent que le président élu Joe Biden reviendra aux normes concernant la coopération multilatérale avec les principaux alliés et les institutions internationales telles que l'OMC, la nouvelle administration sera probablement confrontée à des vents contraires étant donné l'affaiblissement des liens avec les principaux partenaires commerciaux et alliés en raison de mesures prises par son prédécesseur. Cet article donne un aperçu des implications potentielles d'une administration Biden pour le commerce agricole du Canada. Nous commençons par passer en revue les récents chocs commerciaux affectant le commerce agricole du Canada, en mettant particulièrement l'accent sur les mesures commerciales prises par les États‐Unis. Les éléments pertinents de la plateforme du président élu Biden, les considérations affectant la mise en œuvre de cette plateforme et leurs implications pour le commerce agricole canadien sont pris en considération.